Further comments on decay kinetics of isotropic radicals in carbonates - Idrissi, S.; Bentourkia, M.; Debuyst, R. (Ancient TL, 1999)
This work is a continuation of previous investigations on decay kinetics of isotropic radicals in carbonates (Ancient TL, 1997, 15, 30-35). It rules out a model implying only chemical reactions between CO2 and CO3 radicals, questions the use of a sum of first-order kinetics and supports the dispersive second-order equal concentration kinetics with a time-dependent rate constant.